2023
DOI: 10.1126/sciadv.adg1971
|View full text |Cite
|
Sign up to set email alerts
|

176 Lu + clock comparison at the 10 −18 level via correlation spectroscopy

Abstract: The extreme precision of optical atomic clocks has led to an anticipated redefinition of the second by the International System of Units. Furthermore, accuracies pushing the boundary of 1 part in 10 18 and beyond will enable new applications, such as in geodesy and tests of fundamental physics. The 1 S 0 to 3 D 1 optical transition in 176 Lu + h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 46 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…As the ratio between the anharmonic and harmonic terms typically increases when the ion-electrode distance is reduced, it is demonstrated that anharmonic effects become more critical by lessening the ion trap scale. This requires special care, particularly in quantum computing with trapped ions [70,103] or in case of single ion [104][105][106] and multi-ion optical clocks [79,[107][108][109]. On the other hand, it was demonstrated that an increased dodecapole potential generated in an asymmetric linear ion trap (LIT) [97] opens new pathways for exciting applications in mass spectrometry or Coulomb crystals.…”
Section: Of 36mentioning
confidence: 99%
See 1 more Smart Citation
“…As the ratio between the anharmonic and harmonic terms typically increases when the ion-electrode distance is reduced, it is demonstrated that anharmonic effects become more critical by lessening the ion trap scale. This requires special care, particularly in quantum computing with trapped ions [70,103] or in case of single ion [104][105][106] and multi-ion optical clocks [79,[107][108][109]. On the other hand, it was demonstrated that an increased dodecapole potential generated in an asymmetric linear ion trap (LIT) [97] opens new pathways for exciting applications in mass spectrometry or Coulomb crystals.…”
Section: Of 36mentioning
confidence: 99%
“…Furthermore, it is anticipated that the use of compound atomic clocks can enhance the stability of single ion clocks with long clock transition lifetimes to levels comparable to that of optical lattice clocks [80,106]. For ion species with shorter lifetimes, the stability can be improved directly by increasing the number of ions, but this approach requires special care in the selection of the atomic transition and offers the potential for a stability beyond the SQL , which could be a viable method to further improve the stability of optical clocks [109] and provide quantum-limited optical time transfer [87,146] to achieve intercontinental clock comparisons through a common-view node in geostationary orbit (GEO). Several missions such as NASA's Deep Space Atomic Clock (DSAC) or several European Space Agency (ESA) missions are based on deploying optical clocks in space.…”
Section: Ultraprecise Optical Atomic Clocks Based On Ultracold Ions C...mentioning
confidence: 99%
“…With rapid development of laser technology, state-of-the-art optical clocks have now reached an accuracy or frequency stability at the level of 10 −18 [1][2][3][4][5][6] or higher [7,8], which is two orders of magnitude better than the state-of-the-art microwave atomic clocks. At this level of accuracy, optical clocks can play a critical role in redefining the second [9], in searching for variation of fundamental constants [10][11][12][13], and in chronometric leveling [14].…”
Section: Introductionmentioning
confidence: 99%